The true costs of food production in Kenya and Viet Nam - Benfica, Rui; Hossain, Marup; Davis, Kristin E.; Boukaka, Sedi Anne; Azzarri, Carlo (International Food Policy Research Institute, 2024)
Sustainable agrifood systems (AFS) provide food security and nutrition without compromising economic, social, and environmental objectives. However, many AFS generate substantial unaccounted for environmental, social, and health costs. True cost accounting (TCA) is one method that adds direct and external costs to find the “true cost” of food production, which can inform policies to reduce externalities or adjust market prices. We find that for Kenya— considering the entire food system, including crops, livestock, fishing, and value addition sectors at the national level—external costs represent 35 percent of the output value. Social costs account for 73 percent of the total external costs, while environmental costs are 27 percent. In contrast, in Viet Nam, where total external costs represent 15 percent of the output value, the environmental costs (75 percent) dominate social costs. At the subnational level, in the three Kenyan counties (Kisumu, Vihiga, and Kajiado) covered by the CGIAR Research Initiative on Nature-Positive Solutions (NATURE+), external costs (or the true cost gap) represent about 30 percent of all household crop production costs. Those external costs are overwhelmingly dominated by social (84 percent) over environmental (16 percent) externalities. In Viet Nam's Sa Pa and Mai Son districts, external costs represent about 24 percent of all household crop production costs. Environmental externalities (61 percent) are greater than social ones (39 percent). In Kenya, forced labor is the main social (and overall) external impact driven by factors ranging from "less severe" financial coercion to "more severe" forms of physical coercion. Land occupation is the most important environmental impact, resulting from occupation of lands for cultivation rather than conservation, while underpayment (low wages) and low profits are important social costs that are closely associated with the prevailing gender wage gap and occurrence of harassment. Soil degradation is the only other environmental impact, linked with the use of inorganic fertilizers (60 percent of households) and pesticides (36 percent). In Viet Nam, land occupation is the most important external impact, followed by soil degradation and contributions to climate change, primarily due to widespread use of inorganic fertilizers (98 percent of households) and pesticides (93 percent). Underpayment and insufficient income are significant social costs, followed by the gender wage gap and child labor. Crop production systems in Kenya exhibit relatively high labor-related costs compared with nonlabor inputs, with relatively lower intensity in the use of inorganic fertilizer and other chemical inputs and lower crop yields. This production system leads to relatively greater social externalities. Conversely, crop yields in Viet Nam are significantly higher than those in Kenya, likely due to the extensive use of inorganic fertilizers representing the largest direct cost component and leading to a relatively higher level of environmental externalities. Because external costs represent a significant part of the total cost of food production, policy and investments to minimize these costs are essential to a nature-positive AFS that is environmentally sustainable and socially equitable. Strategies to reach this goal include regulatory adjustments, investments in resource efficient infrastructure and technologies that minimize costs, and the prudent management of environmentally impactful production inputs and factors.